AMPK activity is required for the induction of anhydrobiosis in a tardigrade Hypsibius exemplaris, and its potential up‐regulator is PP2A. (6th November 2019) - Kondo, Koyuki; Mori, Masaru; Tomita, Masaru; Arakawa, Kazuharu
Abstract: The anhydrobiotic tardigrade, Hypsibius exemplaris, was previously considered to require de novo gene expression and protein phosphatase 1 (PP1) and protein phosphatase 2A (PP2A) activity for successful anhydrobiosis. These indicate that H. exemplaris has signal transduction systems responding to desiccation stress, with the involvement of phosphorylation events. To this end, we carried out time‐series phosphoproteomics of H. exemplaris exposed to mild desiccation stress and detected 48 phosphoproteins with significant differential regulations. Among them, immediate and successive reduction of phosphorylation levels of AMP‐activated protein kinase (AMPK) was observed. The subsequent chemical genetic approach showed that AMPK was activated during the preconditioning stage for anhydrobiosis, and inhibition of its activity impaired successful anhydrobiosis. As PP2A is known to dephosphorylate AMPK in other organisms, we suggested that decreased phosphorylation levels of AMPK upon mild desiccation stress were caused by dephosphorylation by PP2A. Accordingly, phosphoproteomics of animals pre‐treated with the PP1/PP2A inhibitor cantharidic acid (CA) lacked the decrease in phosphorylation levels of AMPK. These observations suggest that AMPK activity is required for successful anhydrobiosis in H. exemplaris, and its phosphorylation state is possibly regulated by PP2A. Abstract : We performed time‐series phosphoproteomics of an anhydrobiotic tardigrade, Hypsibius exemplaris exposed to mild desiccation stress, and detected immediate and successive reduction of phosphorylation levels of AMP‐activated protein kinase (AMPK). The subsequent chemical genetic approach demonstrated that AMPK was activated during the preconditioning stage for anhydrobiosis, and inhibition of its activity impaired successful anhydrobiosis. These observations suggest that AMPK activity is required for successful anhydrobiosis in H. exemplaris .